Defect Reduction in The Manufacturing Industry: Systematic Literature Review - Mukti Ali Sadikin (Universitas Atma Jaya Yogyakarta, 2023)
Defect reduction is an important aspect of quality improvement in the manufacturing industry, as it directly impacts product quality, customer satisfaction, and operational efficiency. This paper presents a systematic literature review on defect reduction in the manufacturing industry. The study systematically reviewed articles published in the period 2012-2022 in the Google Scholar, ScienceDirect, Emerald, and Springer Link databases. The review aims to provide a synthesis of research studies, methodologies, and best practices employed to minimize defects and enhance overall product quality. This review identifies key themes, challenges, and future directions in defect reduction by analyzing the existing literature, offering valuable insights for researchers and practitioners.